Analysis of Carbon Economic Value Potential - Nurlette, Ahdia; Muspida, Muspida; Metekohy, Stellamaris (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2024)
The study aimed to assess the potential economic value of carbon within PT Strata Pacific's IUPHHK-HA area. The methodology involved collecting, processing, and analyzing numerical data using statistical methods. Sampling techniques included stratified systematic sampling or simple random sampling, with a maximum allowable sampling error of 20%. The study found that the carbon content reserve in tree stands within PT Strata Pacific's IUPHHK area in East Seram Regency, Maluku Province, is 44.95 tonnes per hectare. Assuming a conservative carbon value of US 5 per tonne, the total potential economic value of tree stands and the root shoot ratio in this area ranges from US 12,962,231.50 to US 15,221,643.25. Direct benefits for the local community include improved access to agricultural and plantation roads, social management activities (CSR) by businesses, and job opportunities. These benefits are estimated to have a direct value of Rp 3,525,000,000 per year.